Substrates based on composted sewage sludge for land recultivation - Storoshchuk , Uliana; Malovanyy, Myroslav; Tymchuk, Ivan (Ecological Questions, 2022)
Increasing a large amounts of sewage sludge in Ukraine is an urgent environmental problem that requires the selection of an effective strategy for their disposal. The usage of sludge composting technology leads to the restoration of sludge as a resource and is cost-effective and environmentally sustainable compared to the method of landfilling. The purpose of this research is to carry out bioindication tests of growth substrates based on composted sewage sludge with the subsequent possibility of their usage in the technology of recultivation of landfills for municipal solid waste. The experiment was performed on four types of compost with different modifications of the natural sorbent - zeolite. During the experiment the average percentage of germination of polygamous ryegrass plants (Lolium perenne L.) was determined in the investigated substrates. The mass and length of the aboveground part of the plant and roots were also measured. The results showed that the addition of natural sorbent to substrates has a positive effect on growth and development of plants. This investigation was conducted in accordance with the current norms of national standards of Ukraine: DSTU 7369 (2013), "Wastewater. Requirements for wastewater and its sediments for irrigation and fertilization"; DSTU ISO 11269-1 (2004), "Soil quality. Determination of the effect of pollutants on soil flora. Part 1: Method for determining the inhibitory effect on a root growth"; DSTU ISO 11269-2 (2002), "Soil quality. Determination of the effect of pollutants on soil flora. Part 2: Effects of Chemicals on Germination and Growth of Higher Plants". The experiment was conducted on four types of compost with different modifications of the natural sorbent - zeolite in percentage amounts: 0; 2.5; 5; 7.5, dark-grey gilded soil was used as a control element. In the experiment, the average percentage of germination of polygamous ryegrass plants (Lolium perenne L.) on the studied substrates was determined. The mass and length of the aboveground part of the plant and roots were also measured. The first sprouts of ryegrass began to appear on the 7th day of the experiment. The highest average value on the seventh day of germination was 90% in the control sample with 5% of sorbent content and in K2 substrate in the sample with 7.5% sorbent content. However, the germination of plants in substrates K3 and K4 occurred later compared with substrates K1, K2, and control. For substrate K1 in the sample with a sorbent content of 5%, plant germination was the highest and was 100%. The highest average value of ryegrass stem length is observed in variant K4 in the sample with 0% zeolite content and in variant K1 in the sample without zeolite content the lowest average value of stem length was observed. The K3 and K4 variants have a more developed root system compared to other variants. Based on the obtained data it can be assumed that the most optimal universal component for creating a growth substrate is variant K3 (mixture of "newly picked" and "old" SS) which has not so developed aboveground part but has very branched root system that allows to adapt to various environmental factors and in combination with a small proportion of natural sorbents can be effective for the recultivation of MSW landfills, which in its turn minimizes the need to use a fertile soil layer.